2005
DOI: 10.1007/s11248-005-1773-y
|View full text |Cite
|
Sign up to set email alerts
|

Hairpin RNA-Mediated Silencing of Plum pox virus P1 and HC-Pro Genes for Efficient and Predictable Resistance to the Virus

Abstract: We report the application of the hairpin-mediated RNA silencing technology for obtaining resistance to Plum pox virus (PPV) infection in Nicotiana benthamiana plants. Four sequences, covering the P1 and silencing suppressor HC-Pro genes of an Italian PPV M isolate, were introduced into N. benthamiana plants as two inverted repeats separated by an intron sequence under the transcriptional control of the Cauliflower Mosaic Virus 35S promoter. In a leaf disk infection assay, 38 out of 40 T0 transgenic plants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 30 publications
(28 reference statements)
6
56
1
3
Order By: Relevance
“…Numerous studies have indicated that IR constructs of transgenes can effectively induce RNA silencing to trigger knockout of specific gene expressions (Ali et al, 2010;Allen et al, 2004;Gavilano et al, 2006;Johansen and Carrington, 2001;Kusaba et al, 2003;Liu et al, 2002;Meli et al, 2010;Pandolfini et al, 2003;Segal et al, 2003;Smith et al, 2000;Xiong et al, 2005). In addition, a number of studies showed that IR constructs of transgenes containing virus-derived sequences transformed to plants can effectively protect plants from challenging viruses (Abhary et al 2006;Bucher et al 2006;Chen et al, 2004;Di Nicola-Negri et al 2005;Hammond et al 2006;Lennefors et al 2006;Pooggin et al 2003;Simón-Mateo and García, 2011;Tenllado et al 2003;Tenllado et al, 2004;Vanitharani et al, 2003;Wang et al, 2000). In particular, transient expression of a hpRNA homologous to sequences of Pepper mild mottle virus (PMMoV) caused inhibition of PMMoV accumulation (Tenllado et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have indicated that IR constructs of transgenes can effectively induce RNA silencing to trigger knockout of specific gene expressions (Ali et al, 2010;Allen et al, 2004;Gavilano et al, 2006;Johansen and Carrington, 2001;Kusaba et al, 2003;Liu et al, 2002;Meli et al, 2010;Pandolfini et al, 2003;Segal et al, 2003;Smith et al, 2000;Xiong et al, 2005). In addition, a number of studies showed that IR constructs of transgenes containing virus-derived sequences transformed to plants can effectively protect plants from challenging viruses (Abhary et al 2006;Bucher et al 2006;Chen et al, 2004;Di Nicola-Negri et al 2005;Hammond et al 2006;Lennefors et al 2006;Pooggin et al 2003;Simón-Mateo and García, 2011;Tenllado et al 2003;Tenllado et al, 2004;Vanitharani et al, 2003;Wang et al, 2000). In particular, transient expression of a hpRNA homologous to sequences of Pepper mild mottle virus (PMMoV) caused inhibition of PMMoV accumulation (Tenllado et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…RNA 1 encodes proteins involved in genome replication and expression, and RNA2 encodes the movement protein and the two CPs (Lisa and Boccardo, 1996). RNA silencing has been efficiently used to generate resistance against plant viruses in many ornamental plants (Bucher et al, 2006;Hammond et al, 2006;Tenllado et al, 2004) and in different host systems to obtain resistance against several other viruses (Abhary et al, 2006;Di Nicola-Negri et al, 2005;Lennefors et al, 2006;Pooggin et al, 2003;Tenllado et al, 2003;Vanitharani et al, 2003). Particularly, transgenic expression of pathogen-derived sequences encoding hpRNAs that undergo to an efficient RNA silencing is a new and agricultural sustainable strategy to obtain virus-resistant plants (Smith et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, Anandalakshmi and collaborators and Brigneti and collaborators shown that HC-Pro protein of TEV and 2b of CMV could have this role. A classic paper demonstrated that the inhibition system of the 5' end corresponding to proteins P1 and Hc-Pro was efficient to obtain plants resistant to Plum pox virus (PPV) in tobacco (Di Nicola-Negri et al, 2005). In this same study were tested four regions of the virus genome: (i) nucleotide (nt) 1-733 of the protein corresponding to P1; (ii) nt 954-1603 corresponding to the end of the protein P1 and protein portion of Hc-Pro; (iii) nt 1680-2386 corresponding to the central part of Hc-Pro/P3 and, (iv) nt 1935 to 2613 corresponding to the end of Hc-Pro protein and part of P3.…”
Section: Application Of Rnai To Obtain Transgenic Maize Lines Toleranmentioning
confidence: 99%
“…This has led to the outcome that RNA silencing mechanism can be exploited to generate resistance against viral pathogens. Pathogen derived resistance (PDR) (Sanford and Johnston 1985) strategies based on RNA silencing mechanism have been utilized to develop resistance against RNA or DNA viruses (Chen et al 2004;Di Nicola-Negri et al 2005, Bonfim et al 2007Ramesh et al 2007;Zrachya et al 2007;Vanderschuren et al 2009;Patil et al 2011). Recently, RNAi-based resistance to mixed infection of three different viruses has been reported in soybean plants expressing separate short hairpins from a single transgene (Zhang et al 2011).…”
Section: Introductionmentioning
confidence: 99%